A Novel Tele-Operated Flexible Robot Targeted for Minimally Invasive Robotic Surgery. (March 2015) - Li, Zheng; Feiling, Jan; Ren, Hongliang; Yu, Haoyong
ABSTRACT: In this paper, a novel flexible robot system with a constrained tendon-driven serpentine manipulator (CTSM) is presented. The CTSM gives the robot a larger workspace, more dexterous manipulation, and controllable stiffness compared with the da Vinci surgical robot and traditional flexible robots. The robot is tele-operated using the Novint Falcon haptic device. Two control modes are implemented, direct mapping and incremental mode. In each mode, the robot can be manipulated using either the highest stiffness scheme or the minimal movement scheme. The advantages of the CTSM are shown by simulation and experimental results.